The impact of echinococcosis interventions on economic outcomes in Qinghai Province of China: Evidence from county-level panel data - Cai, Jinshan; Yang, Kefan; Chen, Qihui; Zhao, Quanbang; Li, Jing; Wang, Sen; Yang, Lin; Liu, Yumei (Frontiers in Veterinary Science, 2023)
Echinococcosis can incur substantial economic losses for the livestock industry by causing organ condemnation, delayed growth, and reduced meat and wool output and quality in sheep and cattle, as well as increased surgery costs, hospital care, and decreased productivity in humans. Yet echinococcosis could be prevented and controlled by interventions, such as dog management and deworming, lamb vaccination, slaughter management, and training and public education. Exploiting temporal and spatial variations in the number of intervention measures implemented in 39 counties in Qinghai province of China in 2015-2020, this study assesses the economic impact of echinococcosis interventions using a dynamic difference-in-differences model. The results suggest that echinococcosis interventions brought about substantial economic gains measured by per capita net income of rural residents and per capita gross output of animal husbandry. These economic gains are greater in non-pastoral counties (with a gain in per capita net income of rural residents of 3308 yuan and a gain per capita gross output of animal husbandry of 1035 yuan) than in pastoral counties (with a gain in per capita net income of rural residents of 1372 yuan and a gain per capita gross output of animal husbandry of 913 yuan). They are also greater in counties with echinococcosis infection level-2 (with a human infection rate of 0.1-1% or a dog infection rate of 1-5%) than infection level-1 counties (with a human prevalence rate ≥ 1% or a dog infection rate ≥ 5%). Not only will these economic gains encourage livestock farmers to strengthen their echinococcosis prevention and control practices, but they will also inform public policy on zoonotic disease prevention and control in China and other countries alike.